The effects of tawhidic paradigm on public policy making in Malaysia - Mhd. Sarif, Suhaimi; Ismail, Yusof (2015)
This study examines the conceptualized effects of Tawhidic paradigm on economic policies to promote the growth of halal industry for sustainable wealth creation in Malaysia. Tawhidic paradigm provides guidance to economic policy thinking by relying upon the principles of Qur’an and Sunnah in formulating and implementing policy blueprint and instruments. The current policy thoughts are guided by market forces and sentiments which contributed to unbridled uncertainties and speculation. A Tawhidic paradigm policy thinking and process is developed to help ascertain the level of Tawhidic based policy thinking and practices at policy making, implementation and evaluation. Using personal interview with economic policy makers as method of collecting input, this study reveals that the informants do consider some levels of Tawhidic paradigm but the thoughts appear to be inadequate to help sustain wealth creation.